Reflections on the Document "Vision of the Order, 2002" - Driscoll, Martha E. (Cistercian studies quarterly, 2004)
Reflects on the document "Vision of the Order, 2002," focusing on the meaning of precariousness. Recognition of essential need of others and of God; Total dependence on God as creatures and as adopted children; Secular mentality; Path of transformation in Christ within the monastic setting.